Impact of Liquidity and Leverage on Profitability and Firm Value: Evidence from Oil and Gas Sector on the Indonesia Stock Exchange 2024 Using SEM-PLS - Yulianik yulianik; Bilal Saratoga; Sony Wijaya; Jerry Heikal (Cerdika: Jurnal Ilmiah Indonesia, 2026)
This study examines the impact of liquidity and leverage on profitability and firm value in oil and gas companies listed on the Indonesia Stock Exchange in 2024. The oil and gas sector plays a strategic role in Indonesia’s economy, yet it faces high financial risk due to fluctuating global oil prices, intensive capital requirements, and unstable market conditions. Therefore, understanding the relationship between liquidity, leverage, profitability, and firm value becomes important for investors and corporate management in making financial decisions. The purpose of this study is to analyse the direct and indirect effects of liquidity and leverage on profitability and firm value using profitability as an intervening variable. This research applied a quantitative causal-comparative approach using secondary data obtained from annual financial reports of oil and gas companies listed on the Indonesia Stock Exchange. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that liquidity has a positive and significant effect on profitability, showing that companies with stronger liquidity are more capable of generating profits efficiently. In contrast, profitability has a negative and significant effect on firm value, indicating that increased profitability does not always improve market valuation. These findings suggest that investor perceptions, financial policies, and market conditions may influence firm value more strongly than profitability alone. The study concludes that financial performance and market valuation are not always directly aligned in the oil and gas sector